2014
DOI: 10.1097/mat.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

End-Organ Recovery Is Key to Success for Extracorporeal Membrane Oxygenation as a Bridge to Implantable Left Ventricular Assist Device

Abstract: Preexisting organ dysfunctions are known factors of death after placement of implantable mechanical circulatory support (MCS). Extracorporeal membrane oxygenation (ECMO) may able to stabilize organ function in patients with cardiogenic shock before MCS implantation. Between 2008 and 2012, 17 patients with cardiogenic shock were supported with ECMO before implantable MCS placement. Patient's end-organ functions were assessed by metabolic, cardiac, hepatic, renal, and respiratory parameters. Survival data after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…The duration of support for our bridged patients was approximately 4-5 days, which is similar to most other bridge studies. 4,18 Interestingly a recent article by Durinka et al 10 supported patients with ECMO for an average of 12 days. These investigators reported a 92% survival to discharge for ECMO patients who were transitioned to a dVAD in less than 14 days but reported inferior survival for patients supported >14 days, indicating that prolonged durations of support are associated with an increased risk.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The duration of support for our bridged patients was approximately 4-5 days, which is similar to most other bridge studies. 4,18 Interestingly a recent article by Durinka et al 10 supported patients with ECMO for an average of 12 days. These investigators reported a 92% survival to discharge for ECMO patients who were transitioned to a dVAD in less than 14 days but reported inferior survival for patients supported >14 days, indicating that prolonged durations of support are associated with an increased risk.…”
Section: Discussionmentioning
confidence: 90%
“…5,9 Temporary circulatory support devices appear to be an ideal strategy as these devices are easily deployed, less invasive, and have significantly lower costs compared with dVADs. 10 We investigated TCS strategies used to improve the hemodynamic derangement associated with critical cardiogenic shock and compared clinical stability before dVAD implant as well as postimplant outcomes in patients with profile 1 and profile 2-3 characteristics without TCS. Our analysis indicates that 1) patients on TCS before dVAD implant are sicker at baseline then profile 1 patients without TCS, with a higher use of mechanical ventilation and vasopressors; 2) TCS with ECMO and TH improves hemodynamic parameters before dVAD at levels similar to profile 2-3 patients and better than profile 1 patients without TCS; 3) despite an improvement in hemodynamic parameters with TCS, end-organ function was still impaired with ECMO patients having the highest severity of illness pre-dVAD; and 4) outcomes after dVAD in TCS patients are similar to profile 1 patients without TCS.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for survival from cCS requiring pVA‐ECMO have been well studied . However, clinical data describing factors that affect myocardial recovery in these patients are scarce, despite increasing use of pVA‐ECMO and drastic consequences in cases of failed myocardial recovery .…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…In this complex group of patients, peripheral access is favoured as it does not necessitate a sternotomy or thoracotomy leaving the chest 'virgin' or which may be complex due to previous, often multiple, surgical interventions. At the time of subsequent surgery ECLS can then easily be converted to CPB and continuation of ECLS post-surgery, if required [8,9], can be achieved simply by switching back to an ECLS circuit.…”
Section: Indicationsmentioning
confidence: 99%
“…Extra-corporeal life support (ECLS) for the last 2-3 decades has become an indispensable tool in the armamentarium of physicians and surgeons dealing with patients suffering severe cardio-pulmonary failure [1]. Over the period of time, its utilisation has seen a broadening in terms of indications, age limits and condition of patients [2][3][4][5][6][7][8][9]. Familiarisation with technique, continuous improvement of equipment and changes in strategy in favour of early intervention have helped to improve the survival of patients supported on the ECLS [10,11].…”
Section: Introductionmentioning
confidence: 99%